Waste To Product : Potential Of MG-Rich Gypsum Additive For Strength Improvement Of Peat Soil - Muhammad Syahmi Aiman, Daud (2022)
Around 2 million hectares of peatland can be found in Malaysia, with the majority of it being in coastal regions in Sarawak. In Peninsular Malaysia, peat land has been cultivated with a variety of food crops and palm oil in the states of Johor, Selangor, and Perak. Peat soils are moist in their natural form, with a very high water table at the soil surface. It is also soft because it is organic, which consists of plant components that decay in nature. Peat soil is also known as organic soil. Peat soil has a low bulk density because it is organic in nature. Peat soils become moist due to the high water table and soft soil quality, and it is difficult to walk on undrained peat without sinking. Peat land in Malaysia is often flooded and swampy. Because of this, some areas of peat land have been designated as swamps. However, as development progressed, more and more inorganic mineral soil was depleted, and the border of peat bogs was approached. In certain places in Malaysia, such as in our study where we obtained samples from Pekan to Gebeng, Pahang, there is little choice for the type of soil used because the state has a large proportion of peat land. Peat soils have relatively low shear strengths; however, they have the potential to significantly increase in strength after consolidation. Shear strength is related to many variables, including soil origin, water content, organic content, and degree of decomposition. The shear strength of peat is determined by the drainage conditions. Assessment of undrained shear strength is particularly important because the presence of peat soils is almost always below the groundwater table. The purpose of this research is to show the viability of maintaining peat soil using concrete waste additives as an additive, as well as evaluate the response of peat for soil improvement for construction on it to achieve SDG 11, which is to make settlements inclusive, safe, resilient, and sustainable.